Optimizing the Performance of Identification Affairs in Handling Crime Scenes in order to Disclosure of Criminal Acts of Theft with Aggravated Circumstances as Law Enforcement Efforts - Muhammad Aqlizar Akbar (Police Studies Review, 2022)
Police in charge of Duty enforcement law is naturally expected to uncover perpetrator act criminal with the objective Utilizing the identification method is one of the right choices to realize this. However, the Pekalongan Police Identification Affairs can only identify two crime scenes out of a total of 182 cases of Burglary from 2019 to 2021. This study aims to describe the performance and optimize the performance of identification matters in the handling of crime scenes to reveal the theft with theft. This type of research uses a qualitative approach. Data collection techniques used are interviews, observation, and document studies. Data analysis techniques used include data reduction, data presentation and concluding. The results of the research conducted found the fact that the performance of the identification unit was not optimally influenced by the irregularity of the identification unit personnel in carrying out the SOP for handling crime scenes issued by the Pekalongan Police, the low competence of identification possessed by personnel and the lack of motivation of members in carrying out their duties and developing competence. owned thus, it is necessary to solve the problem.The results of this study were analyzed using the optimization concept and the performance concept along with management theory to describe the first problem and work motivation theory to analyze the second problem. SWOT analysis was used to describe internal and external factors that affect the performance of the Pekalongan Police identification unit in handling crime scenes to disclose the crime of burglary.